2021
DOI: 10.3390/plants10122678
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci and Candidate Genes Associated with Cold-Acclimation and Microdochium nivale Tolerance/Susceptibility in Winter Triticale (x Triticosecale)

Abstract: Tolerance to pink snow mold caused by Microdochium nivale appears after a cold-hardening period and it is an essential, genotype-dependent, complex quantitative trait for the wintering of triticale (x Triticosecale) and other cereals. Despite long-term studies, a marker for the selection of the tolerant genotypes is still insufficiently recognized. Chlorophyll fluorescence has been reported as a sensitive indicator of stress effects on photosynthesis and can be used to predict plant tolerance. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…As mentioned, genetic maps can be used in positioning quantitative trait loci (QTL) that are linked with multiple traits. Up to now, many research studies have described the QTL regions associated with triticale resistance to both biotic and abiotic stresses such as resistance to Fusarium head blight (FHB) [ 17 , 24 , 25 , 26 ], powdery mildew [ 16 , 22 , 27 , 28 ], yellow rust [ 11 , 17 , 29 ], pink snow mold [ 30 , 31 , 32 ], drought [ 33 , 34 , 35 ], and freezing [ 23 , 32 ]. Many studies showed the analysis of QTL regions associated with the important agronomic factors and morphological features of triticale [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Qtl and Candidate Gene Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned, genetic maps can be used in positioning quantitative trait loci (QTL) that are linked with multiple traits. Up to now, many research studies have described the QTL regions associated with triticale resistance to both biotic and abiotic stresses such as resistance to Fusarium head blight (FHB) [ 17 , 24 , 25 , 26 ], powdery mildew [ 16 , 22 , 27 , 28 ], yellow rust [ 11 , 17 , 29 ], pink snow mold [ 30 , 31 , 32 ], drought [ 33 , 34 , 35 ], and freezing [ 23 , 32 ]. Many studies showed the analysis of QTL regions associated with the important agronomic factors and morphological features of triticale [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Qtl and Candidate Gene Analysismentioning
confidence: 99%
“…Such genes that encode multiple proteins can be widely used in modern molecular breeding programs, but so far, not many studies have described such genes identified in crops. In triticale, the information of important candidate genes is still limited [ 16 , 22 , 23 , 28 , 32 , 45 ].…”
Section: Qtl and Candidate Gene Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In Krasnodar territory (south of Russia with little or no snow), M. nivale -caused SM exceeds the epiphytotic level 3–5 times per 10 years, causing yield losses of up to 20% [ 30 ]. In addition, M. nivale has been shown to cause not only SM but also other diseases on cereal crops in the southern parts of Russia [ 23 , 31 ], Poland [ 32 , 33 , 34 ], Denmark [ 35 ], Japan [ 36 ], and China [ 37 ] throughout the growing season.…”
Section: Introductionmentioning
confidence: 99%